Automatic 3D ultrasound segmentation of the first trimester placenta using deep learning - Looney, P; Stevenson, G; Nicolaides, K; Plasencia, W; Molloholli, M; Natsis, S; Collins, S (Institute of Electrical and Electronics Engineers, 2017)
Placental volume measured with 3D ultrasound in the first trimester has been shown to be correlated to adverse pregnancy outcomes. This could potentially be used as a screening test to predict the 'at risk' pregnancy. However, manual segmentation whilst previously shown to be accurate and repeatable is very time consuming and semi-automated methods still require operator input. To generate a screening tool, fully automated placental segmentation is required. In this work, a deep convolutional neural network (cNN), DeepMedic, was trained using the output of the semi-automated Random Walker method as ground truth. 300 3D ultrasound scans of first trimester placentas were used to train, validate and test the cNN. Compared against the semi-automated segmentation, resultant median (1 st Quartile, 3 rd Quartile) Dice Similarity Coefficient was 0.73 (0.66, 0.76). The median (1 st Quartile, 3 rd Quartile) Hausdorff distance was 27 mm (18 mm, 36 mm). We present the first attempt at using a deep cNN for segmentation of 3D ultrasound of the placenta. This work shows that feasible results compared to ground truth were obtained that could form the basis of a fully automatic segmentation method.